2010
DOI: 10.1371/journal.pone.0013865
|View full text |Cite
|
Sign up to set email alerts
|

MEG Responses to the Perception of Global Structure within Glass Patterns

Abstract: BackgroundThe perception of global form requires integration of local visual cues across space and is the foundation for object recognition. Here we used magnetoencephalography (MEG) to study the location and time course of neuronal activity associated with the perception of global structure from local image features. To minimize neuronal activity to low-level stimulus properties, such as luminance and contrast, the local image features were held constant during all phases of the MEG recording. This allowed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…However, the enhanced activity to concentric patterns in V3A/B conflicts with the findings of Mannion et al (2010b), who reported an anisotropy only for starburst patterns. Changes in anisotropic response in V3A/B to polar form centered at eccentricity could underlie this difference, although Swettenham et al (2010) reported qualitatively similar magnitudes of response in V3A/B during observation of starburst and concentric Glass patterns centered at fixation and at eccentricity.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, the enhanced activity to concentric patterns in V3A/B conflicts with the findings of Mannion et al (2010b), who reported an anisotropy only for starburst patterns. Changes in anisotropic response in V3A/B to polar form centered at eccentricity could underlie this difference, although Swettenham et al (2010) reported qualitatively similar magnitudes of response in V3A/B during observation of starburst and concentric Glass patterns centered at fixation and at eccentricity.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, neurophysiological recordings have reported preferences for polar orientation in V1 and V2 neurons and an overrepresentation of neurons preferring concentric orientations (Hegdé & Van Essen, 2007;Mahon & De Valois, 2001). However, Smith, Kohn, and Movshon (2007) found no modulation in activity by polar Glass pattern orientation in V2 neurons, and previous neuroimaging studies have not found differences in polar form response in V1 and V2 (Wilkinson et al, 2000), including to stimuli presented at eccentricity (Swettenham, Anderson, & Thai, 2010). Hence, the role of V1 and V2 in polar form processing remains uncertain.…”
Section: Discussionmentioning
confidence: 97%
“…In this first experiment, we predict that the presence of any global arrangement within a field of randomly oriented Gabor patches should lead to an enhanced N1 component because the N1 has been linked to the presence of a coherent structure (Ohla et al, 2005;Swettenham et al, 2010). Any effect of specific shape attributes, such as the number and placement of corners on the contour, would more likely be evident in later components, including the N220.…”
Section: Methodsmentioning
confidence: 93%
“…The global processing associated with Glass patterns has previously been localized to areas external to the primary visual cortex (Ohla et al, 2005;Vreven & Berge, 2007) with a recent highdensity MEG study suggesting a generator in area V3a (Swettenham et al, 2010). Mannion and Clifford (2011) have shown that both V3 and V4 were involved in processing global arrangements in Glass patterns.…”
Section: Experiments 2 Discussionmentioning
confidence: 99%
See 1 more Smart Citation